Society, politics and Islam : an overview - Moten, Abdul Rashid (Cengage Learning Asia Pte Ltd., 2008)
Malaysia is unique in that it is the only country that has territory on both the mainland and insular regions of Southeast Asia, known as West Malaysia and East Malaysia. West Malaysia, also known as Peninsular Malaysia, has an area of 131,313 sq km (50,700 sq mil and consists of the southern portion or the Malay Peninsula and nearby islands. Thailand borders Peninsular Malaysia on the north, and Singapore lies off the southern coastal tip. Peninsular Malaysia comprises 11 states and the federal territories of Kuala Lumpur and Putrajaya.! East Malaysia, with an area of 201,320 sq km (77,730 sq mi) occupies the northern section oE Borneo Island, as well as offshore islands. East Malaysia shares Borneo with Brunei, which lies on a small section of the northern coast, and with the Kalimantan region of Indonesia, which lies to the south. East Malaysia consists of the states of Sabah and Sarawak, and the Federal Territory of Labuan. East and West Malaysia are separated by about 640 km (about 400 mi) of the South China Sea, and together comprise an area of 329,758 sq km (127,320 sq mi).